E-169 Approach to carotid occlusions presenting with stroke: technical challenges and outcomes from a comprehensive stroke center. (22nd July 2018) - Donegan, B; Akhtar, I; Boutwell, C; Halpin, J; Martin, C; Holloway, W; Akhtar, N
Abstract : Introduction: Carotid artery occlusion in the setting of acute stroke with concurrent intracranial involvement is a serious and deadly combination, and can prove to be a challenging endeavor when encountered. The stroke is usually more severe due to poor collaterals and successful revascularization is difficult to achieve, resulting in a higher morbidity and mortality. We aim to assess the revascularization rates and clinical outcomes in this subset of patients treated with endovascular therapy. Materials and methods: An IRB approved retrospective chart review of cases presenting with acute ischemic stroke with carotid occlusions and concurrent intracranial involvement treated with endovascular therapy over a 4 year period was conducted. Of these reviewed cases, 75 patients had carotid occlusions with intracranial involvement. The carotid T occlusions and critical ICA stenosis with intracranial flow were excluded from the study. Based on the CT and catheter angiogram findings, the 75 patients fell into two groups: Group A (n=35): Carotid occlusion with underlying atherosclerotic disease/dissection resulting in occlusion and were treated with angioplasty and stenting followed by thrombus retrieval. Group B (n=40): No underlying pathology was found and ICA was occluded due to a large embolus to the ICA with no anterograde flow in the ICA. This group was treated with thrombus retrieval alone. Results: Our data shows that the presence of a stent in the ICA does not adversely affect the intracranial recanalization rate (91.4% TICI ≥2  b). There was also no significant increase in hemorrhage rate with revascularization and antiplatelet therapy (2.9%). This finding was especially significant due to the large amount of wake up strokes in our study that were treated with intervention (17.3%). The successful reperfusion rate (TICI ≥2 b) overall in both groups was 82.7%. In the successfully recanalized group, the mortality was 16 % compared to the mortality in the unsuccessfully recanalized group (69.2% ) . Conclusion: Our study results show that it is possible to achieve a high success rate of revascularization and clinical outcomes with an endovascular approach to managing carotid occlusion with intracranial involvement. Disclosures: B. Donegan: None. I. Akhtar: None. C. Boutwell: None. J. Halpin: None. C. Martin: None. W. Holloway: None. N. Akhtar: None.